2020
DOI: 10.3390/v12080879
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Brown Rugose Fruit Virus Contributes to Enhanced Pepino Mosaic Virus Titers in Tomato Plants

Abstract: The tobamovirus tomato brown rugose fruit virus (ToBRFV), a major threat to tomato production worldwide, has recently been documented in mixed infections with the potexvirus pepino mosaic virus (PepMV) CH2 strain in traded tomatoes in Israel. A study of greenhouse tomato plants in Israel revealed severe new viral disease symptoms including open unripe fruits and yellow patched leaves. PepMV was only detected in mixed infections with ToBRFV in all 104 tested sites, using serological and molecular analyses. Six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…On the other hand, the estimated economic impact ranges from USD 46 and 75 billion per year [196]. Other important viruses infecting tomatoes are TMV and Pepino mosaic virus (PepMV; Potexvirus, Alphaflexiviridae), which cause losses of 19-33% and 20-40%, respectively [197][198][199][200]. Tomato leaf curl New Delhi virus (ToLCNDV) is another begomovirus (family Geminiviridae) causing losses in the range of 18-99%, mainly in India and other countries around the world [201][202][203][204].…”
Section: Tomatomentioning
confidence: 99%
“…On the other hand, the estimated economic impact ranges from USD 46 and 75 billion per year [196]. Other important viruses infecting tomatoes are TMV and Pepino mosaic virus (PepMV; Potexvirus, Alphaflexiviridae), which cause losses of 19-33% and 20-40%, respectively [197][198][199][200]. Tomato leaf curl New Delhi virus (ToLCNDV) is another begomovirus (family Geminiviridae) causing losses in the range of 18-99%, mainly in India and other countries around the world [201][202][203][204].…”
Section: Tomatomentioning
confidence: 99%
“…Currently, the only possible control measures are the ones directed at eradication and containment of the infections, such as restriction of access to the production site, disposal of infested plant material, and sanitation measures (EPPO, 2020a). Moreover, a recent research reported that co-infection of ToBRFV with mild strain PepMV resulted in enhanced PepMV accumulation and symptoms characteristic for an aggressive PepMV strain (Klap et al, 2020), bringing additional concerns about the impact of ToBRFV on tomato production.…”
Section: Tobamovirusesmentioning
confidence: 99%
“…Studies of the co-infection of plant viruses in wild and domesticated plants are important for understanding plant virus epidemiology, evolution, and virus–virus interactions; consequently, these investigations will contribute to developing efficient and durable control strategies [ 1 , 2 , 3 , 4 , 5 ]. Co-infections by two or more plant viruses [ 6 , 7 , 8 , 9 , 10 , 11 ], different isolates of the same viruses [ 12 , 13 ], and the presence of quasispecies of the same viruses [ 12 , 14 , 15 , 16 , 17 ] in wild and domesticated plants seem likely to be common in nature [ 18 , 19 , 20 ]. Plants of the genus Narcissus in the family Amaryllidaceae are known as wild or domesticated plants, although it is difficult to draw a boundary distinguishing between these plants in Japan.…”
Section: Introductionmentioning
confidence: 99%